The Effectiveness of Youtube as a Student Learning Media (Study at the Faculty of Social and Political Sciences, University of Bengkulu) - Samosir, Fransiska Timoria; SAmosir, Fransiska Timoria; SAmosir, Fransiska Timoria (Record and Library Journal, 2018)
Background of the study: In the era of glogalization the use of the internet has developed very dramatically. This is indicated by the use of gadgets among students who are always connected to the internet. Students like to find information in real or audiovisual form. The presence of YouTube also provides great results to the current generation. This is what makes the basis for learning how to use YouTube as a learning medium among students. Purpose: The purpose of this research is to study learning from YouTube as a media for student learning. Method: The method used in this research is descriptive qualitative. Findings: The results of this study indicate that students have a high level of gadget usage and are always connected to the internet. Students Almost every day Open the youtube application on their gadget. Conclusion: Yotube is used as a learning media that supports in adding knowledge and supporting the task of lectures. Learning to use YouTube by FISIP students can be seen effectively from the usability, accuracy, and distribution space of yotube media.